2010
DOI: 10.1152/ajpregu.00516.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin-like growth factor-I, insulin, and leucine on protein turnover and ubiquitin ligase expression in rainbow trout primary myocytes

Abstract: The effects of insulin-like growth factor-I (IGF-I), insulin, and leucine on protein turnover and pathways that regulate proteolytic gene expression and protein polyubiquitination were investigated in primary cultures of 4-day-old rainbow trout myocytes. Supplementing media with 100 nM IGF-I increased protein synthesis by 13% (P < 0.05) and decreased protein degradation by 14% (P < 0.05). Treatment with 1 microM insulin increased protein synthesis by 13% (P < 0.05) and decreased protein degradation by 17% (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 89 publications
(132 reference statements)
6
58
0
1
Order By: Relevance
“…In addition to providing tight glycaemic control, insulin has other potentially beneficial effects for skeletal muscle. Studies performed in animals or in vitro have shown that insulin is anabolic (by promoting protein synthesis [135] and inhibiting the UP [136]), is potentially anti-inflammatory [137], improves dyslipidaemia [138] and is neuroprotective [139]. Consistent with an anabolic role for insulin in humans, a post mortem study of critically ill patients has shown an increase in skeletal muscle protein concentration in those who were treated with intensive insulin therapy compared with controls [119].…”
Section: Bioenergenetic Failure Oxidative Stress and Glycaemic Controlmentioning
confidence: 99%
“…In addition to providing tight glycaemic control, insulin has other potentially beneficial effects for skeletal muscle. Studies performed in animals or in vitro have shown that insulin is anabolic (by promoting protein synthesis [135] and inhibiting the UP [136]), is potentially anti-inflammatory [137], improves dyslipidaemia [138] and is neuroprotective [139]. Consistent with an anabolic role for insulin in humans, a post mortem study of critically ill patients has shown an increase in skeletal muscle protein concentration in those who were treated with intensive insulin therapy compared with controls [119].…”
Section: Bioenergenetic Failure Oxidative Stress and Glycaemic Controlmentioning
confidence: 99%
“…In mammalian muscle, this pathway is stimulated by the pro-inflammatory cytokine TNF- and, once activated, is alone sufficient to induce major atrophy via upregulation of MuRF1 (Glass, 2005). The role of the IGF-Akt pathway in inhibiting atrophy appears conserved in teleosts, as IGF-I induced phosphorylation of both Akt and FOXO proteins and concurrent downregulation of MuRF1 and MAFbx was observed in salmonids (Cleveland and Weber, 2010;Seiliez et al, 2010). The NF-kB pathway may also have a role in controlling protein breakdown in salmonids, as there was a large increase in mRNA expression of both p65 (a subunit of the NF-kB complex) and the NF-kB target genes MuRF1 and UBE2H during fasting (Macqueen et al, 2010a;Bower and Johnston, 2010b).…”
Section: Protein Degradationmentioning
confidence: 99%
“…Cell cultures derived from these fish expressed the fluorescent protein once myoblasts started to fuse and differentiate to form myotubes. Primary cell cultures have already been used to examine various pathways in teleosts including insulin and IGF regulation of glucose transporters (Diaz et al, 2009) and TOR signaling (Seiliez et al, 2008;Cleveland and Weber, 2010). Myogenic cells isolated from Atlantic salmon withdrew from the cell cycle and entered a quiescent state following starvation induced by the withdrawal of amino acids and serum.…”
Section: In Vitro Models Of Muscle Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…To exclude the off-target effects of LY294002 on other protein kinases including DNA protein kinase (DNA-PK) and mTOR, PI3K activity was blocked by wortmannin, another selective and irreversible PI3K inhibitor at nanomolar concentrations (Powis et al, 1994;Ptasznik et al, 1997). Owing to the unstable nature of wortmannin in culture medium (with half-life between 8 and 13 minutes) (Holleran et al, 2003), 50 nM wortmannin was replenished every 2 hours during the 9 hours of in vitro maturation (at 0 hours, 2 hours, 4 hours and 6 hours of culture), as suggested by other studies (Cleveland and Weber, 2010;Franch et al, 2002;Shpetner et al, 1996). Consistently, treatment of wortmannin impaired migration of the meiosis I spindle to the cortex.…”
Section: Resultsmentioning
confidence: 99%